One Way or Another: A Report of Toyota's Company Social Performance - Zwelibanzi Mpehle; Analtha Farhansyah; Muhammad Ilham Wardhana Haeruddin; M. Ikhwan Maulana Haeruddin (Har Press Indonesia, 2021)
As one of the prominent brands in the global automotive market, Toyota needs to provide satisfaction to stakeholders to maintain its reputation. The purpose of this article is to explain how Toyota ensures these satisfactions by implementing Corporate Social Performance (CSP). Toyota aims to grow into a company that will be good corporate citizenship that is trusted by all their stakeholders and support the society affluent over all the business activities. This is important as the result of the CSP is shaping consumer's perception toward brand in terms of brand personality and playing a central role in sustaining Toyota's long-term objectives. This paper employs research methods by systematically reviewing the relevant literature. Inclusion criteria will be that (a) sources contain the key terms of